Depression, Risk Preferences and Risk-Taking Behavior - Deborah A. Cobb-Clark; Sarah C. Dahmann; Nathan Kettlewell (Institute of Labor Economics (IZA), 2019)
Depression affects the way that people process information and make decisions, including those involving risk and uncertainty. Our objective is to analyze the way that depressive episodes shape risk preferences and risk-taking behaviors. We are the first to address this issue using large-scale, representative panel data that include both behavioral and stated risk preference measures and a theoretical framework that accounts for the multiple pathways through which depression affects risk-taking. We find no disparity in the behavioral risk preferences of the mentally well vs. depressed; yet depression is related to people's stated risk preferences and risk-taking behaviors in ways that are context-specific. Those who are likely to be experiencing a depressive episode report less willingness to take risks in general, but more willingness to take health risks, for example. We investigate these patterns by developing a conceptual model – informed by the psychological literature – that links depression to risk-taking behavior through the key elements of a standard intertemporal choice problem (e.g., time preferences, expectations, budget constraints). This motivates a mediation analysis in which we show that differences in risk-taking behavior are largely explained by depression-related disparities in behavioral traits such as locus of control, optimism and trust. Overall, we find that there is no overarching tendency for those who are depressive to engage in either more or less risk-taking. Instead, the decision-making context matters in ways that largely align with our theoretical expectations.
Keywords: D91; I12; D14; 330; risk preferences; depression; mental health; risk-taking